Development in infancy - Arterberry, Martha E.; Bornstein, Marc H. (New York: Routledge, 2024)
"Development in Infancy reflects many new discoveries that have transformed our understanding of infants and their place in human development, with an emphasis on 21st century research. Organized topically, the book covers physical, perceptual, cognitive, language, and social development, in addition to describing theories of development, contexts of development, research methods, and implications of research in infancy for social policies and interventions. Key issues in infancy studies-those having to do with how nature and nurture transact and with interrelations among diverse domains of development-are woven throughout the text. The text also emphasizes infancy as a unique stage of the life cycle"--
Revised edition of: Development in infancy : a contemporary introduction / Marc H. Bornstein, Martha E. Arterberry, Michael E. Lamb. Fifth edition. 2014.
Includes bibliographical references and index.
Keywords: Infants -- Development; Infant psychology